Analysis Level of Difficulty in The Aspect of Analytical Thinking Skills in Science Learning - Astuti, Dwi Setyo; Sajidan, S; Suciati, S; Masykuri, Mohammad (Universitas Muhammadiyah Surakarta, 2025)
This study discusses analysis level of difficulty in the aspect of analytical thinking skills in science learning with the aim of providing insights on how students and educators can address these difficulties, ultimately contributing to a more effective science education system that fosters critical and analytical thinkers. By using the research methods The study used a quantitative methods using Rasch analysis and Confirmatory Factor Analysis (CFA) to determine the level of difficulty of students' analytical thinking skills aspects. Based on the analysis, the aspects of